Nfkbia-driven neuroinflammatory pathways mediate depression following spinal cord injury - Yang, Aichun; He, Guoyuan; Song, Yanling; Wen, Yujun; Xia, Hechun; Gu, Shenhong (Frontiers in Molecular Neuroscience, 2025)
IntroductionSpinal cord injury (SCI) frequently leads to severe motor impairments and psychological issues, particularly depression, which negatively affects overall quality of life. This study seeks to clarify the relationship between SCI and depression by employing a comprehensive approach that includes behavioral assessments, transcriptomic profiling, and molecular analyses.MethodsWe established a weight-drop model of SCI and randomly assigned mice to Sham and SCI groups. Behavioral assessments included the Open Field Test (OP), Sucrose Preference Test (SP), and Tail Suspension Test (TS). We conducted transcriptomic analyses using datasets related to SCI and major depressive disorder (MDD) sourced from the GEO database. The hub gene, Nfkbia, was identified with Cytoscape software and validated through RT-PCR. Western blotting was utilized to measure the protein levels of IκB-α (encoded by Nfkbia) and phosphorylated p65 (p-p65). Additionally, we examined hippocampal histopathology and measured pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α).ResultsFollowing SCI, mice displayed abnormal behaviors in the OP, SP, and TS, suggesting the development of depression-like symptoms. In light of these observations, we analyzed publicly available transcriptomic datasets related to SCI and depression, identifying 16 common differentially expressed genes. Functional enrichment analysis showed that these genes were primarily associated with biological processes linked to inflammatory responses. We constructed a protein–protein interaction network that highlighted four potential key genes (Nfkbia, Fkbp5, Sgk1, and Cdkn1a). Subsequent molecular biology experiments confirmed that Nfkbia was downregulated after SCI, resulting in an increase in inflammatory factor production and the emergence of depression-like behaviors in mice.DiscussionOur results suggest that neuroinflammation plays a crucial role in the onset of depression after SCI. This is supported by the activation of the IκB/p65 signaling pathway and the dysregulation of inflammatory cytokines. These findings align with clinical observations of mood disorders in patients with SCI and reflect known patterns of inflammatory cytokine dysregulation. This study underscores the significance of anti-inflammatory treatments and comprehensive neuropsychiatric management strategies in the rehabilitation of SCI patients.